GESTOSIS SCORE AS A PREDICTIVE TOOL FOR PREECLAMPSIA IN HYPERTENSIVE PREGNANCIES: A PROSPECTIVE COHORT STUDY (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Preeclampsia is a major contributor to maternal and perinatal morbidity and mortality worldwide, particularly in developing countries. Early identification of women at risk remains challenging because of the multifactorial nature of the disease. The Gestosis scoring system, based on maternal clinical risk factors, offers a simple, practical, and cost-effective method for early prediction of hypertensive disorders of pregnancy. Materials and Methods: This prospective cohort study was conducted in a private tertiary care hospital over a period of six months, from July 2025 to December 2025. A total of 350 pregnant women beyond 36 weeks of gestation with gestational hypertension or newly detected hypertension were initially assessed for eligibility. After exclusion of 20 women due to incomplete records and failure to meet the study criteria, 330 women were included in the final analysis. Detailed clinical history, obstetric parameters, and relevant biochemical data were collected. Gestosis score was calculated for each participant, and all patients were followed up till delivery and during the postpartum period. Statistical analysis was performed to determine the association between gestosis score and the development of preeclampsia. Results: The proportion of severe preeclampsia was significantly higher among women with a gestosis score greater than 3 (42.7%) compared to those with a score of 3 or less (6.4%), with a relative risk of 6.7 (p85 mmHg), anemia, and increased body mass index (p